Abnormal Blink Reflex and Intermuscular Coherence in Writer's Cramp - Choudhury, Supriyo; Singh, Ravi; Chatterjee, Payel; Trivedi, Santosh; Shubham, Shantanu; Baker, Mark R.; Kumar, Hrishikesh; Baker, Stuart N. (Frontiers in Neurology, 2018)
Background: Writer's cramp (WC) is a task-specific focal hand dystonia presenting with pain, stiffness and/or tremor while writing. We explored the involvement of cortical and brainstem circuits by measuring intermuscular coherence (IMC) and pre-pulse inhibition (PPI) of the blink reflex. Methods: IMC was measured in 10 healthy controls and 20 WC patients (10 with associated tremor) while they performed a precision grip task at different force levels. Blink responses were evaluated in 9 healthy controls and 10 WC patients by stimulating the right supraorbital nerve and recording surface EMG from the orbicularis oculi muscles bilaterally. PPI involved conditioning this stimulation with a prior shock to the right median nerve (100 ms interval), and measuring the reduction in the R2 component of the blink reflex. Results: Significant IMC at 3–7 Hz was present in WC patients, but not in healthy controls. Compared to healthy controls, in WC patients the R2 component of the blink reflex showed significantly less PPI. IMC at 3–7 Hz could reliably discriminate WC patients from healthy controls. Conclusion: Cortical or sub-cortical circuits generating theta (3–7 Hz) oscillations might play an important role in the pathogenesis of WC. Moreover, the lack of PPI implicates abnormalities in brainstem inhibition in the emergence of WC. IMC may merit further development as an electrodiagnostic test for focal dystonia.